Correction of the post-irradiation T1 relaxation effect for chemical exchange-sensitive MRI: A phantom study - Chung, Julius Juhyun; Jin, Tao (Frontiers in Physics, 2022)
ABSTRACT Purpose: In many pulse sequences of chemical exchange-sensitive MRI including multi-slice chemical exchange saturation transfer (CEST) or chemical exchange sensitive spin-lock (CESL), there is a finite time delay between the irradiation preparation and the imaging acquisition, during which the T1-relaxation reduces the chemical exchange contrast and affects the accuracy for volumetric imaging. We propose a simple post-acquisition method to correct this contamination. Methods: A simple formula was derived to evaluate the cross-slice T1-relaxation contamination in multi-slice echo-planar imaging (EPI) after the irradiation preparation. CEST and CESL experiments were performed on phantoms to examine the accuracy of this approach. Results: Theoretical derivation showed that the cross-slice T1-relaxation contamination in multi-slice EPI imaging can be corrected by the signals of each slice at a parameter that suppresses the signal, e.g., at the water frequency for CEST, or with very long spin-lock pulse for CESL. This formula was confirmed by the results of phantom experiments, for both long and short irradiation durations with and without a steady-state, respectively. To minimize the effect of B0 inhomogeneity in the CEST experiment, a more accurate measurement of the signal at water frequency can be achieved with a higher pulse power and shorter duration. Conclusion: We proposed and validated a simple approach to correct the cross-slice T1-relaxation effect, which can be applied to volumetric CEST and CESL studies acquired by multi-slice EPI, or other imaging modalities with similar T1-relaxation contamination.